2023
DOI: 10.47836/pjssh.31.2.05
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using PhET in Changing Malaysian Students’ Attitude to Learning Physics in a Full Virtual Environment

Abstract: This study investigated the effect of physics inquiry learning using PhET Interactive Simulation on form four students’ attitudes toward physics in a fully virtual environment during the COVID-19 pandemic in Malaysia. This quantitative study employed the Quasi-Experimental Design by administering the Attitude Toward Physics Lesson Scale (ATPLS). Fifty-nine form four students from a rural school located in Selangor, Malaysia, participated in this study. The control group (n1= 25) was taught in the standard them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The authors suggested pairing PhET Interactive Simulation with other learning tools or platforms to provide better instant feedback and guidance to students. 28 Overall, this study demonstrated the potential of technology tools, student-centered pedagogy, and innovative teaching methods to overcome challenges in online chemistry teaching and improve students' engagement, learning outcomes, and interest in the subject. The findings suggest that with effective adaptation and exploration of suitable platforms and teaching approaches, chemistry teachers can achieve successful outcomes even in unstable and unpredictable situations, such as the COVID-19 pandemic.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 69%
See 1 more Smart Citation
“…The authors suggested pairing PhET Interactive Simulation with other learning tools or platforms to provide better instant feedback and guidance to students. 28 Overall, this study demonstrated the potential of technology tools, student-centered pedagogy, and innovative teaching methods to overcome challenges in online chemistry teaching and improve students' engagement, learning outcomes, and interest in the subject. The findings suggest that with effective adaptation and exploration of suitable platforms and teaching approaches, chemistry teachers can achieve successful outcomes even in unstable and unpredictable situations, such as the COVID-19 pandemic.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 69%
“…However, it is essential for teachers to evaluate the suitability of each platform for their specific teaching goals and consider the needs and preferences of their students. This is because recent study suggested that PhET Interactive Simulation might not be suitable to be applied during the entire virtual environment to enhance students’ attitudes in physics lessons due to personal matters, technical issues, school training lessons, and extraneous influences. The authors suggested pairing PhET Interactive Simulation with other learning tools or platforms to provide better instant feedback and guidance to students …”
Section: Discussionmentioning
confidence: 99%
“…One of the many benefits of using PhET simulations in the classroom is that they encourage students to think in a constructivist fashion. This, in turn, makes learning more engaging by enabling students to draw on both their existing knowledge and the outcomes of the simulations [13]. Students can enhance their ability to think creatively about abstract phenomena and gain a better understanding of visual concepts through the use of PhET simulations.…”
Section: Introductionmentioning
confidence: 99%